Stimulantia Effect Of Single Bulb Garlic Extract (Allium Sativum Var.Solo Garlic) in Swiss Webster Mice - Ika Buana Januarti (Jurnal Farmasi Indonesia, 2020)
Stimulant is an agent that stimulates the central nervous system thereby increasing physical and mental abilities and minimizing fatigue. The use of synthetic caffeine stimulants of 10 mg / kg BW is known to have side effects of increasing total cholesterol and increasing LDL, therefore alternative stimulants from natural ingredients are needed. Natural materials that have been studied contain flavonoids and phenolic as a stimulant compound is a single garlic bulbs. The purpose of this study was to determine the stimulant effect of a single garlic bulbs ethanolic extract on mice from the difference in swimming time. The research experimental used Pre test and Post test control design. Sample of this research used mice which were divided into 6 groups. Group 1 pretest dose 5 g / kgBB, group 2 (negative control), group 3 (caffeine), group 4 extract dose 5g / kgBB, group 5 dose 10g / kgBB and group 6 dose 20g / kgBB. Data was analyze using one way Anova continued with Post Hoc test. The group of single garlic bulb ethanolic extract dose 20 g / kgBB had the highest stimulant effect with 222,722 minutes fatigue time difference and statistically have significant difference (p <0.05) than the negative control group. Group of single garlic bulb extract can influence the time of fatigue of mice by extending the swimming time of mice so that it has a longer fatigue time which means it has a stimulant effect